0558 Sleep Disordered Breathing and Right Ventricular Electrocardiographic and Functional Characteristics in Group 1 Pulmonary Arterial Hypertension. (27th May 2020) - Bhat, A S; Wang, L; Kaur, S; Nawabit, R; Highland, K; Park, M; Jellis, C; Kwon, D; Hill, N; Mehra, R; Pvdomics, P
Abstract: Introduction: Right ventricular (RV) electrophysiologic and functional alterations related to sleep disordered breathing (SDB) in pulmonary arterial hypertension (PAH) are not well understood. We hypothesize an association between SDB and RV electrophysiological/functional measures in World Symposium of Pulmonary Hypertension (WSPH) Group 1 PAH. Methods: The NHLBI multicenter PVDOMICS study (NCT02980887) enrolls patients with PAH undergoing a battery of assessments including home sleep apnea testing(NOX-T3, Carefusion®) or with historical sleep study data. Logistic(OR, 95%CI) and linear(beta coefficients, 95%CI) regression models adjusted for age, sex, race, body mass index (BMI, kg/m 2 ), PAH medications, supplemental oxygen(O2), positive airway pressure(PAP) were used to assess associations of SDB(apnea hypopnea index, (AHI), ≥ 3% desaturations(hypopnea), percentage recording time with SaO2<90% (TRT<90%) with electrocardiographic measures: RV hypertrophy(RVH), right bundle branch block(RBBB), and right axis deviation(RAD), echocardiographically-derived RV systolic pressure(RVSP) and RV ejection fraction(RVEF) from cardiac MRI. Analyses were performed based on an overall significance level of 0.05, using SAS software (version 9.4, Cary, NC). Results: The analysis consisted of 182 PAH participants with age: 52.5 ± 13.9 years, 71.4% female, 88.9% Caucasian, BMI:30.3±7.8 kg/m 2, RVEF: 37.3±11.6, and RVSP: 67.0±23.4. None of the electrocardiographic measures were associated with AHI and only RVH was significantly associated with TRT<90% (1.25:1.09, 1.43), p=0.001. Although AHI was not associated with RVSP, a 10% increase in TRT<90% was associated with a 2.60mmHg increase in RVSP (2.60:1.44, 3.76), p<0.001. Each 10-unit increase in AHI was associated with a 2.72% reduction of RVEF (-2.72:-4.89, -0.56), p=0.014, and each 10-unit increase in TRT<90% was associated with a 0.72% reduction of RVEF (-0.72:-1.38, -0.06), p=0.033. Conclusion: We identify nocturnal hypoxia as a predictor of RV electrophysiological and functional alterations even after consideration of confounding factors. SDB as determined by AHI was also more so associated with reduced RVEF than hypoxia. Future mechanistic studies should focus on further elucidation of SDB and nocturnal hypoxia on pathogenesis of RV dysfunction in PAH. Support: U01HL125218/U01HL125205/U01HL125212/U01HL125208/U01HL125175/U01HL125215, U01HL125177/Pulmonary Hypertension Association